زیبایی‌شناسی در رمان‌های نو - مهرگان نظامی‌زاده (Naqd-i Zabān va Adabīyyāt-i Khārijī, 2013)
We know the inarticulate language We read the signs without reference mark. The evolution of the novelists of this country would result in the displacement of their interest, of the bottom to the form, without any doubt in connection with the design positivist of the end of the XIX century, as for the abandonment of the style balzacian in favor of new romantic forms. From the principle of the Art for art’s sake formulated by Theophiles Gauthier, the writers and the Parnassian poets identified the transcendence of the art by the negation of its definite barriers. Such a design requires the exclusion of the personal identity of the artist; identity influenced in any case by its social environment and its historical period. They are successively surrealism and the existentialism which teach him how to flee demanding realities and to break the last ramparts of ego interior. The free man and released of any engagement test, however, even of nature existentialist. The death of God in Occident involves this time that of the Man so that the art can appear as Untied Beauty of any external interpretation and description. As the history of such an experiment, how does the New Novel let appear essential prestige of the Art in abstracting it and by stripping it? Where reside the common and divergent aspects of the style of the new novelists in order to reveal the Hidden Beautiful?